THE EFFECT OF HEALTH EDUCATION ON THE ATTITUDE TOWARDS EXCLUSIVE BREASTFEEDING: A STUDY AMONG PRIMIGRAVIDA WORKING WOMEN IN SEMARANG, INDONESIA - Novita Sari; Isy Royhanaty; Rose Nurhudhariani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Exclusive breastfeeding is breast milk was given to infants until the age of 6 months without any food additives. Based on a preliminary study by interviews conducted by researchers on December 12 to 26, 2014 in Bulu Lor Public health center there are 7 out of 10 working primigravida women who don’t know about exclusive breastfeeding. Aims: This study aimed to determine the effect of health education on the attitude of working primigravida women in second-trimester toward exclusive breastfeeding. Methods: This research uses a quantitative research with a quasi-experimental method with preexperimental research design using one group pretest-posttest design. The population in this study were all primigravida second-trimester who worked as many as 58 people with of all working primigravida second-trimester who met the inclusion criteria. Using total sampling technique. By bivariate analysis test of difference mean dependent (paired t-test). Results: Based on the results of research on the effect of health education on the attitude of working primigravida women in second-trimester toward exclusive breastfeeding, There is a significant difference in the attitude toward exclusive breastfeeding of working primigravida women before and after providing health education. With the p-value of 0.000 < 0.05. Conclusion: There is an influence of health education on the attitude of working primigravida women in second-trimester toward exclusive breastfeeding.